THE MODERATING ROLE OF INFORMATION TECHNOLOGY IN THE PERFORMANCE OF BAITUT TAMWIL MUHAMMADIYAH IN CENTRAL JAVA INDONESIA - usamah; Hilda Lutfiani (International Journal of Islamic Business and Economics (IJIBEC), 2021)
This study aimed to analyze the moderating role of Information Technology in the performance of Baitut Tamwil Muhammadiyah in Central Java, Indonesia. The target population was members of this Islamic Microfinance Institution. Data from 2015 to 2018 in the Central Java Sharia Office was used to obtain a sample size of 14 from 21 BTMs. Multiple Regression Analysis was then applied to analyze this data and explain the relationship between variables. The results showed that independent variables, including CAR, NPF, and BOPO ratios are positively correlated with ROA (Return on Assets) of BTM, except FDR. Information technology system moderation variables including FDR_SYSTEM and BOPO_SYSTEM significantly and positively affect ROA, while CAR_SYSTEM and NPF_SYSTEM are negatively correlated with the returns on total assets of the institution. In general, BTM should use I.T. for excellent performance and join academics and other stakeholders to increase awareness of the benefits of these computer-based systems in Islamic Microfinance institutions.